2021
DOI: 10.1186/s13071-021-05097-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Anopheles stephensi in Ethiopia provides insight into patterns of spread

Abstract: Background The recent detection of the South Asian malaria vector Anopheles stephensi in the Horn of Africa (HOA) raises concerns about the impact of this mosquito on malaria transmission in the region. Analysis of An. stephensi genetic diversity and population structure can provide insight into the history of the mosquito in the HOA to improve predictions of future spread. We investigated the genetic diversity of An. stephensi in eastern Ethiopia, where detection suggests a range expansion int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Each sample is colored by Wolbachia haplotype, where haplotype 1 is colored in blue, haplotype 2 is colored in red, and haplotype 3 is colored in yellow. Haplotypes 1 and 2 are representative of Wolbachia supergroup A, and haplotype 3 is representative of supergroup B. Anopheles stephensi COI haplotypes are designated on the clades that they represent according to Carter et al [ 45 ]. Anopheles maculatus was used as an outgroup (KT382822).…”
Section: Resultsmentioning
confidence: 99%
“…Each sample is colored by Wolbachia haplotype, where haplotype 1 is colored in blue, haplotype 2 is colored in red, and haplotype 3 is colored in yellow. Haplotypes 1 and 2 are representative of Wolbachia supergroup A, and haplotype 3 is representative of supergroup B. Anopheles stephensi COI haplotypes are designated on the clades that they represent according to Carter et al [ 45 ]. Anopheles maculatus was used as an outgroup (KT382822).…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis of samples collected in the Horn of Africa suggest it may have originated in southern Asia and the Arabian Peninsula. Studies in Ethiopia have found evidence of high genetic diversity and geographical structuring, and concluded that the populations found in south-eastern parts of the country were more recent than those in the north-eastern areas [ 31 ]. This report, together with an earlier analysis concluded that An.…”
Section: Understanding and Responding To The Threatmentioning
confidence: 99%
“…This report, together with an earlier analysis concluded that An. stephensi populations in this region were closely linked to samples from Pakistan, and therefore most likely originated from south Asia as opposed to the Arabian Peninsula [ 2 , 31 ]. In eastern Ethiopia, even samples collected far inland were often found along transport routes [ 19 ], suggesting that the geographical dispersal may be driven by human activities and that there may be a common origin.…”
Section: Understanding and Responding To The Threatmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in most of these studies, mosquitoes were offered additional blood meals from the same host species as the original challenge (e.g., human for primary and additional blood meals) (reviewed in [3] but see [6]). While proximity to livestock is a well-known risk factor for malaria incidence, surveillance of natural populations of mosquitoes routinely finds evidence of blood from multiple host species while co-incident with human Plasmodium infections [7][8][9][10][11][12][13]. However, it is generally assumed that the nutritional benefits of a non-human blood meal can enhance vectorial capacity by promoting vector survival and population density [14][15][16][17][18][19][20], although it is unclear if it can influence parasite development rates directly.…”
Section: Introductionmentioning
confidence: 99%